A study of perception on natural hazards and risk by residents of mountainous areas and factors influencing their choice of residential location - Coo, Kathreen S.
This study examines Benguet province residents' perception on natural hazards and its risks, how they cope with these and how they choose where to reside. Benguet is a mountainous province that experiences many natural hazards because of its physical characteristics (generally high elevation and sloping terrain), and because it is earthquake-prone and within the high typhoon incidence zone. Despite repeated experience of hazardous events, damage to property and loss of lives, people continue to locate residences in the province's mountainous areas. The perception on natural hazards of household survey respondents and participants of FGDs may be described as follows : clear notion of what the hazards are (identified were landslides, flooding, strong winds, heavy rains and earthquake); varied ranking (for level of concern) given to different hazards, especially across categories of years of residency, farming/non-farming groups and municipalities; and varying perception on the effects of natural hazards and climate change on households, also across categories of residency and municipalities. In general, perception on natural hazards and risks differed across individuals, and was found to be shaped most significantly by hazard experience as proxied by years of residence and municipality location. Individual characteristics, such as age and sex; have generally not been found to be significant determinants; these variables according to literature are mediating variables that help shape perception indirectly through their effects on hazard exposure and experience. Information sources constitute another important factor of hazard perception, next to hazard experience. Sources of information 'with the personal touch', such as word of mouth, barangay tanods and community assembly, were found to be important sources for some groups of respondents. Actions to prepare for natural hazards named by survey respondents include participation in community related activities and preparation of household level plans and survival kits, all of which were mentioned at high percentages by respondents. Actions before, during ad immediately after a hazard significantly and consistently varied across municipality location and across categories of years of residence; but mixed results were seen across the other characteristics, age, sex and source of income. Actions of respondents tabulated by rankings of hazards showed mixed results indicating the ambiguity of the link between hazard perception and protective action taken.The gap between perception and action is seen in the 8% of household survey respondents who would not evacuate when notified to do so. Understanding what shapes action is a step towards creating effective hazard communication materials and tools. Factors for residential location choice were identified in FGDs to include personal/cultural, livelihood, environmental, and access to service. The physical features of the actual location of the residential housing clusters, however, have implications on their exposure to natural hazards; but susceptibility to natural hazards was not a primary consideration in residential location choice. In general, findings from the analysis of factors of residential location choice showed positive factors to outweigh natural hazards considerations.